2003
DOI: 10.1108/02683940310494412
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress among managers: a Malaysian survey

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
58
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 10 publications
4
58
0
2
Order By: Relevance
“…Selye (1974) suggested that learning to live with other people is one of the most stressful aspects of life (cited from Manshor et al, 2003). For teachers who move into unfamiliar cultures, acculturative stress can cause lowered mental health (e.g., confusion, anxiety, depression) and feelings of alienation; those who feel marginalized can become highly stressed.…”
Section: Stress In the Higher Education System And Its Effects On Orgmentioning
confidence: 99%
See 4 more Smart Citations
“…Selye (1974) suggested that learning to live with other people is one of the most stressful aspects of life (cited from Manshor et al, 2003). For teachers who move into unfamiliar cultures, acculturative stress can cause lowered mental health (e.g., confusion, anxiety, depression) and feelings of alienation; those who feel marginalized can become highly stressed.…”
Section: Stress In the Higher Education System And Its Effects On Orgmentioning
confidence: 99%
“…Unpleasant or dangerous physical conditions such as crowding, noise, air pollution, or ergonomic problems (Smith, 2000;Fairbrother & Warn, 2003;Manshor et al, 2003;Reskin, 2008) as well as unrealistic deadlines, low levels of support from supervisors are known to cause occupation stress (Johnson et al, 2005; Work Safe, 2006). Selye (1974) suggested that learning to live with other people is one of the most stressful aspects of life (cited from Manshor et al, 2003).…”
Section: Stress In the Higher Education System And Its Effects On Orgmentioning
confidence: 99%
See 3 more Smart Citations